Awareness of the Brand in Sayum Saba Village through Social Media Marketing and Tourist Attraction Building - Sekar Chalifah Segara; Ihsan Effendi; Adelina Lubis (Universitas 17 Agustus 1945 Semarang, 2024)
Sayum Saba Village is one of the tourist villages in Karo Regency, North Sumatra, which has interesting natural and cultural tourism potential. However, the public is still not familiar with this village very much. Dengan menggunakan quantitative methods with a descriptive approach, this study aims to analyze the influence of social media marketing and tourist attractions on brand awareness of Sayum Saba Village. The findings show that social media marketing and tourist attractions have a positive impact on brand awareness of Sayum Saba Village. In order to promote tourist villages, this research suggests that Sayum Saba Village create natural and cultural tourist attractions, work with influencers and travel bloggers, and step up the quantity and quality of its social media marketing. It is envisaged that this study will assist Sayum Saba Village in raising its profile and drawing in more visitors.